THEORETICAL FOUNDATIONS OF GENDER RESEARCH IN LINGUISTICS - Yusupova, Gulkhumor (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article aims to provide theoretical information about the history and methodology of the development of linguistic genderology in different periods. The researches of Uzbek, German, English, Russian linguists and sociologists on gender are widely discussed and highlighted in this article. In addition, the article presents an analysis of gender marked Uzbek and German lexical and phraseological units.